Methylated of genes behaving as potential biomarkers in evaluating malignant degree of glioblastoma. Issue 12 (27th March 2017) - Wen, Wan‐Shun; Hu, Sheng‐Li; Ai, Zhibing; Mou, Lin; Lu, Jing‐Min; Li, Sen
Abstract : Abnormal methylation genes usually act as oncogenes or anti‐oncogenes in the occurrence and development of tumor, indicating their potential role as biomarkers in the evaluation of malignant tumor. However, the research on methylation's association with glioblastoma was rare. We attempted to figure out whether the methylation of genes could serve as the biomarker in evaluating the malignant degree of GBM. Methylation microarray data of 275 GBM patients have been downloaded from The Cancer Genome Atlas (TCGA) dataset. Logistic regression was used to find the methylated genes associated with the malignant degree of patients with the tumor. Functional enrichment analysis and network analysis were further performed on these selected genes. A total of 668, 412, 470, and 620 genes relevant with the methylation or demethylation were found to be associated with the malignant degree, Grades 1–4 of tumor. The higher the degree of malignant tumor, the higher of its methylation degree of its corresponding genes. GO and KEGG analysis results showed that these methylated genes were enriched in many functions as cell adhesion, abnormal transcription, and cell cycle disorder, etc. Of note, CCL11 and LCN11 were found to be significantly related to the progression of GBM. Critical genes associated with cell cycle as CCL11 and LCN1 may play essential roles in the occurrence, development, and transition of glioblastoma. More research was needed to explore its potential molecular mechanism. Abstract : Abnormal methylation genes usually act as oncogenes or anti‐oncogenes in the occurrence and development of tumor, indicating their potential role as biomarkers in the evaluation of malignant tumor.A total of 668, 412, 470 and 620 genes relevant with the methylation or demethylation were found to be associated with the malignant degree, Grades 1–4 of glioblastoma. Of note, CCL11 and LCN11 were found to be significantly related to the progression of GBM.